Prevention of Tuberculosis: Literature Review - Lucya, Vita (KnE Life Sciences, 2021)
This study is a literature review on the control and prevention of Tuberculosis, involving both medical treatment and community behaviour. The journal search produced six journal articles from 2018-2020that match the inclusion criteria. Based on the articles that have been reviewed, the data shows that there are several preventive methods that can reduce the incidence of tuberculosis, including increasing clean living habits by practicing the correct ethics of coughing and sneezing, using masks, and opening windows every morning so that ventilation and sunlight can enter into the room. Keywords: prevention, transmission, tuberculosis